The intellectual perception and some specific physical abilities as a function to predict the standard score of youth soccer players (16-18 years) - Adel Abdul Baser Ali Haıtham (Selcuk University, 2014)
This study aimed at identifying: Predictive equations of predicting with standard score of skill performance of soccer players with the significance of both intellectual perception and individually and collectively specific physical abilities to which they contribute. The research sample included 24 players in the age group of 16 - 18 years. They were intentionally selected from Al-Masry Club, and Sports Port Fouad Club in Port Said. The researcher has used 22 players out of the basic sample, and from the same community to conduct a scoping study. The researcher has used the tests and measures to collect basic data for this study. The most important results indicated that The predictive equation of predicting the standard score of soccer players' performance from the age of 16- 18 years in the significance of specific physical abilities and the variables of the intellectual perception to which they contribute has been as follows: Standard score of the soccer players' performance from the age of 16-18 years = -173.97 - 0.142 (Kinetic Sense) - 14.372 (Successive Stations) + 0.181 (Barrow Zigzag Run Test) + 0.389 (Bending the trunk to bottom) + 6.326 (stop ball from different heights) 10.129 (Running for 30Ã-5 times) + 0.752 (Running for 3m) + 0.996 (Associated Emotional Condition) + 0.997 (Auditory perception) + 1.382 (Standing Vertical Jump) + 0.092 (Wall Passing) + 8.727 (Running, walking for 800m).